Clustering technical approaches of world class pole vaulters - Cassirame, J.; Eustache, E.; Sanchez, H.; Czingon, H.; Homo, S.; Frère, J. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Pole vault performance has been mainly biomechanically investigated to point out performance determinants [1]. Several key parameters were highlighted such as speed, grip, size of athletes or take-off (TK) angle. From this, many coaches and scientists published studies describing ideal technical approaches of pole vaulting for performance [2]. Today, observations of top vaulters raise questions about the classical technical model that is well-documented. The goal of this study was to identify potential technical profiles using actual measurements taken during official competitions and to examine these profiles from athlete`s characteristics and mechanical perspective.